2021
DOI: 10.1093/abm/kaaa122
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity, Functional Impairment, and Emotional Distress: A Coping Mediation Model for Persons With Cancer

Abstract: Background Comorbid disease in cancer patients can substantially impact medical care, emotional distress, and mortality. However, there is a paucity of research on how coping may affect the relationship between comorbidity and emotional distress. Purpose The current study investigated whether the relations between comorbidity and emotional distress and between functional impairment and emotional distress were mediated by thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…These findings not only suggested the different protective mechanisms for quality of life dimensions but also mirrored previous suggestions as to the variabilities in the effect of a given coping strategy in various situations, especially during the course of cancer ( Reddick et al, 2005 ; Ahlstedt Karlsson et al, 2020 ). In terms of behavioral disengagement, some studies suggested that when aggregated with denial to form disengagement coping, behavioral disengagement could contribute to heightening emotional distress and physical wellbeing, respectively, in higher states of functional impairment ( Merluzzi et al, 2021 ) and lifetime stressful events ( Langford et al, 2017 ; Merluzzi et al, 2019 ). Some other studies also suggested venting to be a function of maladaptive mental processes of pessimism in evoking cancer distress ( David et al, 2006 ), which also showed its lower levels to be functional in terms of arm subscale in the current patients with mastectomy ( n = 153).…”
Section: Discussionmentioning
confidence: 99%
“…These findings not only suggested the different protective mechanisms for quality of life dimensions but also mirrored previous suggestions as to the variabilities in the effect of a given coping strategy in various situations, especially during the course of cancer ( Reddick et al, 2005 ; Ahlstedt Karlsson et al, 2020 ). In terms of behavioral disengagement, some studies suggested that when aggregated with denial to form disengagement coping, behavioral disengagement could contribute to heightening emotional distress and physical wellbeing, respectively, in higher states of functional impairment ( Merluzzi et al, 2021 ) and lifetime stressful events ( Langford et al, 2017 ; Merluzzi et al, 2019 ). Some other studies also suggested venting to be a function of maladaptive mental processes of pessimism in evoking cancer distress ( David et al, 2006 ), which also showed its lower levels to be functional in terms of arm subscale in the current patients with mastectomy ( n = 153).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to know comorbidities and complications associated with the indexed disease; in this study, e.g., the selected diagnoses, type 2 diabetes and severe osteoarthritis, are both known as disorders that are accompanied with a high level of comorbidity and disability (48, 49). In addition, as indicated by the knowledge gained so far, the level of adaptation to chronic disease (in association with providing an adequate social and service support) could be of the utmost importance for avoiding negative emotions and achieving a satisfactory level of psychological resilience and well-being (13,16,50,51). Education of older individuals with chronic diseases in changing unproductive into productive coping with stress mechanisms, is considered the right intervention approach to improving adaptation to chronic diseases (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Unsuccessful coping with chronic diseases may cause emotional distress, which in turn may diminish internal psychological resources (resilience) and change the one`s perception of the stressful situation and of the availability of social support, thus maintaining and/or aggravating the feeling of loneliness (13,15). Such course of aging can lead to the development of the "loneliness trait", characterized by the set of psychosocial characteristics and speci c comorbidity patterns, that an individual having this trait possesses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In addition, there are mindfulness 3,4 and exercise-based 5 interventions as well as those that foster social support, 6 coping, 7 self-efficacy 8 and problem-solving 9 in order to improve some aspect of quality of life. However, cancer patients' lives are not only defined by stress that is closely related to cancer care such as managing symptoms and other comorbid diseases, 10 but also current life problems (e.g., financial, insurance, workrelated, home life), [11][12][13] and major life events 14 (e.g., accident, death of someone, job loss). Importantly, many such issues may be exacerbated by a cancer diagnosis and its treatment, which may impact engagement in cancer care and quality of life.…”
Section: Introductionmentioning
confidence: 99%